2009
DOI: 10.1590/s1984-82502009000300015
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genotoxicity and cytotoxicity of "lixeira" (Curatella americanaL.) λ using the prophage induction test (SOS inductest)

Abstract: Curatella americana L., commonly known as "lixeira" in Brazil, has been used in folk medicine to treat ulcers and inflammations. The purpose of the present work was to evaluate the cytotoxic and genotoxic potential of the ethanolic extract of C. americana stem bark using the prophage λ induction test (SOS inductest). To evaluate the cytotoxicity of this plant, after treatment with different concentrations of the extract, Escherichia coli WP2s(λ) cultures were diluted in M9 buffer, inoculated into LB plates, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Scytodes fusca and in almost all of Brazil, especially in the Cerrado biome (Sarmiento and Monasterio 1983;Vilar et al 2009), further sampling effort from the barks of C. americana should be made. This may provide more precise information on the natural history of T. gomezi.…”
Section: Family Scytodidae Blackwall 1864mentioning
confidence: 99%
“…Scytodes fusca and in almost all of Brazil, especially in the Cerrado biome (Sarmiento and Monasterio 1983;Vilar et al 2009), further sampling effort from the barks of C. americana should be made. This may provide more precise information on the natural history of T. gomezi.…”
Section: Family Scytodidae Blackwall 1864mentioning
confidence: 99%
“…Fruits are ovoid, dark reddish-brown to black, arillate, and glabrous. [9] Plants of Dilleniaceae family play an important role in traditional medicine, and some of them are used for arthritis, diabetes, [10,11] dysentery, hepatitis, blennorrhagia, [12] and to treat gastrointestinal disorders, inflammation, [13][14][15][16] hemorrhoids, wounds, [17] and leishmanial ulcers. [18] Studies have shown that extracts from of them as well as their isolated compounds possess diverse biological activities, including antihemorrhagic, [19] antiinflammatory, antioxidant, antimicrobial, [20,21] antitumoral, [22] antiulcer, immunological, [23] and cancer chemoprevention.…”
Section: Introductionmentioning
confidence: 99%
“…However, many plants can also pose health risks since they exhibit cytotoxic (Silva et al, 2012), genotoxic (Vilar et al, 2009a), and mutagenic activities ). Long-term use of genotoxic compounds can cause DNA damage and promote the development of degenerative diseases, such as cancer .…”
Section: Introductionmentioning
confidence: 99%